SKEMATA WACANA HUMOR STAND UP COMEDY INDONESIA - Fitri Fitri; Mahyuni Mahyuni; Sudirman Sudirman (Center of Language and Cultural Studies, 2019)
This qualitative research design was conducted to describe the schema, cohesion, coherence, and context contained in the stand-up comedy performed by famous comics (performer of stand up comedy) in Indonesia. The data were in the form the text of stand up comedy performed by Raditya Dika, Ernest Prakarsa, and Pandji Pragiwaksono. The source of the data was video-audio stand up comedy on Youtube http://www.youtube.com. The data gathered and analyzed grounded in theory of schematic, cohesion, coherence, and humorous discourse. The results show that the schemata appear in the setup section and each schema appears based on the experience of comics. The schema appears variously including dating, children, family, education, personal experience, social and so forth. The cohesion found in the stand-up comedy performed by the comics is only a few and without coherence in it. The context rising also depends on the main theme of stand up comedy.